2006
DOI: 10.1128/cvi.13.3.309-313.2006
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Contamination in Commercially Available Pokeweed Mitogen Contributes to the Activation of Murine Macrophages and Human Dendritic Cell Maturation

Abstract: Commercially available pokeweed mitogen (PWM) has been reported to activate macrophages, leading to production of proinflammatory cytokines and nitric oxide (NO). However, we found that polymyxin B (PMB), a specific inhibitor of endotoxin activity, inhibited the PWM-induced expression of proinflammatory cytokines and NO and the activation of Toll-like receptor 4 (TLR4). A kinetic-turbidimetric Limulus amebocyte lysate assay demonstrated that commercial PWM contained substantial endotoxin, over 10 4 endotoxin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Interestingly, the findings not only confirmed the functionally significant levels of LPS contamination in the plasmaderived thrombin preparations, but also demonstrated the scope and severity of the LPS contamination problem for a host of other factors and compounds relevant to CNS pathophysiology. The results are also consistent with several isolated findings from the immunology literature describing the effects of LPS contamination on macrophage/ monocyte activation by a few selected commercial-grade protein preparations including heat-shock protein-60 (Gao and Tsan, 2003b), −70 (Gao and Tsan, 2003) and the lectin pokeweed mitogen (Yang et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the findings not only confirmed the functionally significant levels of LPS contamination in the plasmaderived thrombin preparations, but also demonstrated the scope and severity of the LPS contamination problem for a host of other factors and compounds relevant to CNS pathophysiology. The results are also consistent with several isolated findings from the immunology literature describing the effects of LPS contamination on macrophage/ monocyte activation by a few selected commercial-grade protein preparations including heat-shock protein-60 (Gao and Tsan, 2003b), −70 (Gao and Tsan, 2003) and the lectin pokeweed mitogen (Yang et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Studies in the immunology literature have suggested that the activation of peripheral macrophages/ monocytes by commercially available preparations of heat-shock protein (Bausinger et al, 2002;Gao and Tsan, 2003a,b) and pokeweed mitogen (Yang et al, 2006) were due to LPS contamination. Recently, we reported that a number of microglial activation responses induced by commercial-grade preparations of thrombin were due to protein contaminants (Hanisch et al, 2004;Weinstein et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, 100 pg/ml LPS (ϳ2 EU/ml) was found to be the minimum concentration that could effectively activate RAW 264.7 macrophages (34,35). Our results are consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 93%
“…It is known that PWM is mitogenic to both T and B cells, but it is unlikely that commercially available PWM is a completely purified lectin, and it has been pointed out that commercially available PWM might be contaminated with large amounts of endotoxin and unidentified proteins. 31,32) According to a previous report, 33) PWM is composed of at least five isolectins (designated Pa-1 to Pa-5), and it has been reported that Pa-1 is mitogenic to both murine T and B cells, whereas Pa-2, Pa-4, and Pa-5 are T cell-specific mitogens. Probably, a comparative study of Pa-1 and CEL-I would provide useful information on the structure-activity relationships of mitogenic lectins.…”
Section: Resultsmentioning
confidence: 99%